Psychosocial predictors of adolescents' violence in Ibadan metropolis, Oyo State, Nigeria (2011)
The study investigated whether psychosocial variables (self-concept, self-efficacy, self-esteem, peer pressure, parental discipline, family type, home environment, gender and early physical signs of violence) predicate anti-social behaviours in the society. The research design adopted was a descriptive survey method. The sample consisted of 250 adolescents (140 males and 110 females) randomly drawn from 15 Senior Secondary Schools in the 11 local government areas of Ibadan metropolis. The average age was 16.5. The instrument used for the study was constructed by the researchers titled "Adolescents' Violence Measuring Scale (AVMES)". Three research questions were raised and the collected data were analysed with the use of Multiple Regression Analysis and Pearson Product Moment Correlation analysis, at 0.05 level of significance. The results revealed a significant joint and relative contributions of all independent variables to adolescent violence. The researchers recommended that parents, teachers and policy makers should team-up to train students to develop high self-esteem, positive self-concept, high self-efficacy and other positive issues of life so as to reduce violence and other antisocial behaviours among adolescents